Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Produk Cireng Frozen Food Pada CV. â€œXYâ€ - Fakhri, Rizqi; Rofidah, Siti (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research was conducted on CV. XY, the purpose of this study was to determine the effect of product quality on purchasing decisions at CV. XY, with the population in this study were 780 people and a sample of 89 people. Data collection was carried out through questionnaires and data analysis techniques used with a significant level of 0.05 were validity test, reliability test with Cronbach alpha, t test, and simple linear regression analysis and analysis of determination R Square (R^2). The results of the analysis and the data of this study using SPSS version 21, the results of the simple linear regression equation are Y = 13,121 + 0,775 X. Based on the results of research on the t test, the value of t_count> t_table (8,272> 1,987) then the results of this study indicate that product quality has a significant effect on purchasing decisions. Based on the data obtained from the results of the correlation analysis between variables X and Y variables obtained R Square (RÂ²) of 0.440 or 44.0%, this shows that the percentage of the contribution of the influence of the independent variable on the dependent variable is 44.0% while the remaining 56, 0% is influenced by other variables not examined in this study